Dynamic investigations of liquid crystalline elastomers and their constituents by 2H NMR spectroscopy. Issue 13 (8th December 2018) - Milavec, Jerneja; Resetic, Andraz; Bubnov, Alexej; Zalar, Bostjan; Domenici, Valentina
ABSTRACT: Several side-chain liquid single crystalline elastomers (LSCEs) were investigated by means of 2 H NMR spectroscopy focusing on the temperature dependence of the spectral line width and spectral shape, as well as the T-dependence of spin–lattice and spin–spin relaxation times ( T 1 and T 2 ). All measurements were performed at the Larmor frequency of 76.753 MHz for 2 H. The LSCEs were prepared in the form of monodomain films by using either 2 H-labelled monomers (or co-monomers), 2 H-labelled cross-linkers or 2 H-labelled molecular probes free to diffuse in the LSCE matrix. In all cases, deuterons are on the phenyl moiety. The main features of the measured 2 H NMR properties (static and dynamic ones) in these different cases were discussed and compared with those of low-molecular-weight mesogens (i.e. the same molecules used as monomers or co-monomers in the side-chain LSCEs) in the nematic and smectic A phases. Among all investigated LSCE samples, those 2 H-labelled on the cross-linker sites present distinct properties either on the 2 H NMR spectral line width and spectral shape in the paranematic and in the nematic phases, which can be interpreted in terms of director reorientational dynamics in the intermediate–slow motional regime, taking into account the inherent local director misalignment of LSCEs. Graphical Abstract: